Penegakan Hukum Udara Terhadap Pesawat Udara Asing Yang Melanggar Yurisdiksi Negara Indonesia - Anna Santa Siregar; Irma Halima Hanafi; Welly Angela Riry (Faculty of Law Universitas Pattimura, 2026)
State sovereignty over airspace is a fundamental principle in international law as affirmed in the 1944 Chicago Convention. Indonesia as a sovereign country has the full and exclusive right to regulate and secure airspace over its land and waters. However, the practice of violating airspace by foreign aircraft—both civilian and state—still occurs and raises questions about the effectiveness of national law enforcement and its harmonization with international law. This research uses normative juridical methods with legislative, conceptual, and case approaches. The results of the study show that normatively Indonesia already has an adequate legal basis through Law Number 1 of 2009 concerning Aviation and Government Regulation Number 4 of 2018 concerning the Security of the Airspace of the Republic of Indonesia, including the mechanism of interception and forced landing. However, in implementation, there are still obstacles in the form of limited surveillance systems, the lack of optimal integration of air defense, and diplomatic considerations for large countries. Therefore, strengthening air defense capacity and consistency of law enforcement are the main prerequisites for Indonesia's air sovereignty to be not only normative, but also factually effective.